2015
DOI: 10.1055/s-0035-1557773
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Guttiferones from Renewable Parts of Symphonia globulifera by Centrifugal Partition Chromatography

Abstract: The aim of this study was to investigate the species Symphonia globulifera, a source of polycyclic polyprenylated acyl phloroglucinols such as guttiferone A, which is known to exhibit a variety of biological activities including noticeable antileishmanial properties. Our goal was the identification and the quantification of guttiferone A in different renewable parts of S. globulifera and its preparative isolation. To the best of our knowledge, there is no data concerning its mechanism of action. Consequently, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Guttiferones A (1) and C (6) were obtained as described. 24 Trifluoroacetic acid and formic acid were of reagent grade from Fluka. Gradient grade HiPersSolv acetonitrile from VWR was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Guttiferones A (1) and C (6) were obtained as described. 24 Trifluoroacetic acid and formic acid were of reagent grade from Fluka. Gradient grade HiPersSolv acetonitrile from VWR was used.…”
Section: Methodsmentioning
confidence: 99%
“…1 Guttiferone A and oxy-guttiferones, the xanthone derivatives guttiferone A (1) shows a broad spectrum of activity, such as anti-HIV, 18 cytotoxic, 19 trypanocidal, 20 antiplasmodial, 21 leishmanicidal, 22 and antibacterial 23 effects, and can be extracted on a gram scale. 24 It belongs to the polycyclic polyprenyl acyl phloroglucinol family (PPAPs) which has been exclusively isolated from the plants of family Guttiferae. Some semisynthetic derivatives has been synthetized through the modification of catechol moiety and the phloroglucinol ring in order to reduce its toxicity and increase its antiparasitic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Guttiferone A ( 2 ) was extracted from Symphonia globulifera extract following a reported procedure . Hyperforin ( 3 ) was extracted from a petroleum ether extract of Hypericum perforatum following a reported procedure .…”
Section: Methodsmentioning
confidence: 99%
“…The results showed that renewable organs/tissues could be used as starting material for the production of PPAPs, thereby reducing the impact on the biodiversity. We also succeeded in isolating the guttiferone A ( 2 , Chart ) from the latex in large quantity, permitting its use in biological research. , Therefore, we decided to test the guttiferone A ( 2 ), structurally close to the guttiferone G, on SIRT1, and to carry out subsequent structure–activity relationship studies. Other PPAPs such as hyperforin ( 3 ) and its derivative aristoforin ( 4 , Chart ) were also included in the study to serve as positive control.…”
Section: Introductionmentioning
confidence: 99%